2005
DOI: 10.1002/jmor.10387
|View full text |Cite
|
Sign up to set email alerts
|

Binucleate trophoblast giant cells in the water buffalo (Bubalus bubalis) placenta

Abstract: The binucleate trophoblast giant cells (BNC) of the water buffalo, Bubalus bubalis, placenta were studied, with emphasis on the synthesis of BNC-specific proteins. Placentomal tissues of 27 water buffalos (2-10 months of pregnancy) were processed for light and electron microscopy. The frequency of BNCs was 20% of the trophoblastic cells in 2-3-month placentas and increased to 27% in the later stages. Ultrastructurally, binucleate cells displayed a prominent granular endoplasmic reticulum and Golgi apparatus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
1
17
0
10
Order By: Relevance
“…Statistical analysis was performed by a Student t test, and differences were considered significant at a P value of Ͻ0.05 (indicated by an asterisk). placenta of B. bubalis (3) and Tragelaphus placental morphology is very similar to that of the genus Bos (7).…”
Section: Fusion Activities Of Berv-k Env Proteinsmentioning
confidence: 70%
“…Statistical analysis was performed by a Student t test, and differences were considered significant at a P value of Ͻ0.05 (indicated by an asterisk). placenta of B. bubalis (3) and Tragelaphus placental morphology is very similar to that of the genus Bos (7).…”
Section: Fusion Activities Of Berv-k Env Proteinsmentioning
confidence: 70%
“…Assis Neto (2005) descreveu a membrana coriônica em bovinos e identificou que as células trofoblásticas estão entremeadas entre as células trofoblás-ticas gigantes, ambas as células são globosas com citoplasmas claros e bem granulares. Winsatt (1980) e Carvalho et al (2006 observaram que as células binucleadas do córion em diferentes espécies são semelhantes entre si. Estas características morfológicas da célula trofoblás-tica mononucleada e da célula gigante indicam uma semelhança entre a membrana coriônica de bubalinos e de outras espécies de ruminantes.…”
Section: Discussionunclassified
“…Carvalho et al (2006), descrevem em seu trabalho uma grande quantidade de estruturas capazes de produzir e estocar proteínas, indicando a semelhança entre os resultados obtidos.…”
Section: Discussionunclassified
“…The binding of PHA-L indicates the presence of N-acetyllactosamine-type glycans (Hammarströ m et al 1982, Kaneda et al 2002. This kind of glycosylation appears to be conserved within the bovids, since PHA-L also binds to granules of ovine (Jones et al 1994) and water buffalo (Carvalho et al 2006) BNC. In sheep, it has been demonstrated that PHA binds to PAG, which was immunopurified with the SBU-3 antibody (Atkinson et al 1993).…”
Section: Discussionmentioning
confidence: 99%